Fracture of Testicle - Wani, Imtiaz; Wani, Shayiq; Malik, Altaf; Bhat, Irfan H; Banay, Vigar; Thoker, Mukhtar (Journal of Nepal Paediatric Society, 2013)
Testicular fracture is a rare injury. A testicular fracture occurring after being kicked in the scrotum in a young male is presented. Patient presented two days after trauma. Pain and swelling were presenting symptoms. Ultrasonography was used for diagnosis. Exploration of scrotum with repair of fracture was done and patient recovered well. DOI: http://dx.doi.org/10.3126/jnps.v32i3.6074 J. Nepal Paediatr. SocVol.32(3) 2012 259-260